Emissions control at pulp mills: A case study on the implementation of combined SOx and NOx removal technology - Myrberg, Samuel (My University, 2024)
In this study the implementation of a combined NOx and SOx scrubber at pulp mills are evaluated using Södra´s site in Mönsterås as a case study. The study aimed to evaluate how the current process would be impacted by implementing the scrubber when achieving the same emission reduction as the current best available technology for large combustion plants in regard to chemical consumption, needed process modifications and possibility to treat the scrubber effluent with the current wastewater treatment system. To achieve this a scrubber was designed and modelled using Aspen Plus investigating different sulfite oxidation rates and flue gas data was collected from the site. From the results it was concluded that the impact on consumption of chemicals was of low significance except for NaOH and oxidised white liquor and that the effluent should not be treated in the current wastewater treatment plant due to large amounts of sulfate in the effluent which if not removed can affect the wastewater treatment negatively. In regard to process modifications this depends on which oxidising agent is used, for H2O2 the right temperature conditions can already be achieved but for ClO2 the temperature needs to be further decreased which could be achieved through flue gas condensation.
Keywords: SOx; NOx; pulp mills; recovery boiler; lime kiln; sulfite oxidation; wastewater treatment